PEMBUATAN MESIN PENGADUK ADONAN UNTUK MENINGKATKAN PRODUKSI PADA USAHA KECIL PENJUAL MARTABAK - Widodo, Rahmat Doni; Khumaedi, Muhammad (Universitas Negeri Semarang, 2017)
This devotion activity carried out with the aim to help problems that were be- ing faced by small business sellerof martabak “Bangka”. Activity specific target of this de- votion is to generate the external aspects of production such as: making dough mixer machine of sweet martabak that is rotated with electric motor. The methods used for the imple- mentation of this activity was done in various ways that support each other, namely: coordina- tion, machine building, training of machine operating, accompanying partners during the ac- tivities in progress and evaluating activity results. The result of this devotion activity is dough stirring machine with ¼ PK that time of the stirring becomes five times faster, stirring dough results become smoother, production increases, as well as income and increasing its profits